SYSTEMATIC METHODS OF CHEMICAL PROCESS DESIGN - Biegler, Lorenz T., author 263952; Grossmann, Ignacio E., author 408162; Westerberg, Arthur W., author 182619 (Upper Saddle River, New Jersey : Prentice Hall, Inc., 1997)
Brings together all the information engineers and researchers need to develop efficient, cost-effective chemical production processes.The book presents a systematic approach to chemical process design, covering both continuous and batch processes. Starting with the basics, the book then moves on to advanced topics. Among the topics covered are: flowsheet synthesis, mass and energy balances, equipment sizing and costing, economic evaluation, process simulation and optimization. The book also covers specific chemical processes such as distillation systems, reactor networks, separation, and heat exchange networks. It shows how to build more flexible processes, including multiproduct batch processes.Any researcher or practicing engineer involved in designing chemical processes.